33 Dietary Impacts on Rumen, Vaginal, and Uterine Microbiota in Beef Heifers. (8th March 2022) - Pickett, Autumn; Cooke, Reinaldo F; Colombo, Eduardo; Mackey, Shea; Filho, Ramiro Oliveira; Dalmaso, Gabriela; Poole, Rebecca K; Pohler, Ky G
Abstract: This experiment investigated the effects of diet composition on rumen, vaginal, and uterine microbiota of beef heifers. Fifteen rumen-cannulated, pubertal Angus-influenced heifers were used in a replicated 3 x 3 Latin square design (28-d periods and 21-d washout intervals). Dietary treatments included diets based on (as-fed) 100% grass hay (HF), 61% grass hay + 39% corn-based concentrate (INT), or 25% grass hay + 75% corn-based concentrate (HG). Treatments were offered individually to heifers once daily at 2% BW. Heifers also received 280 g/d of a mineral mix containing melengestrol acetate. Rumen, vaginal, and uterine samples were collected on d 0 and 28 of each period for bacterial profiling of the 16S rRNA gene and pH measurement. Data were analyzed using the MIXED procedure of SAS using results from d 0 as independent covariates, and heifer as the experimental unit. Ruminal pH on d 28 was greater (P < 0.01) in HF compared with INT and HG, and greater (P < 0.01) in INT compared with HG. Uterine and vaginal pH on d 28 did not differ among treatments (P > 0.10). In the rumen, Bacteriodetes was the most abundant phylum with the relative abundance being significantly greater (P < 0.01) in HF and INT (64.9 and 62.6%, respectively) when compared with HG (53.9%). Prevotella was the most abundant genus of bacteria within the rumen but did not differ (P > 0.10) by dietary treatment. While there were no significant differences (P > 0.10) for bacterial phyla in vaginal samples, Prevotella was the most abundant genus with the relative abundance being significantly greater (P < 0.01) for the HG (18.62%) when compared with HF and INT (7.78 and 10.35%, respectively). There were no significant differences (P > 0.10) for bacterial phyla in uterine samples, and while Prevotella was the most abundant, it was unaffected (P > 0.10) by diet. Therefore, diet impacted rumen microbiota and appears to have an influence on vaginal microbiota of beef heifers.